2016
DOI: 10.1016/j.trci.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol inactivates AMPK and reduces tau phosphorylation in a tau mouse model of Alzheimer's disease

Abstract: IntroductionThe use of antipsychotic medications in Alzheimer's disease has been associated with an increased risk of mortality in clinical trials. However, an older postmortem literature suggests that those with schizophrenia treated in an era of exclusively conventional antipsychotic medications had a surprisingly low incidence of tau pathology. No previously published studies have investigated the impact of conventional antipsychotic exposure on tau outcomes in a tau mouse model of AD.MethodsIn two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Indeed, pretreatment with D2R‐specific antagonists did not prevent the apoptosis‐inducing effect of aripiprazole but rather strengthened it, clearly demonstrating that D2R signaling is not responsible for the aripiprazole‐induced apoptosis in breast cancer cells. It has previously been reported that treating mice with haloperidol reduces tau phosphorylation via D2 blockade‐mediated inactivation of AMPK . In this study, breast cancer cells activate the AMPK pathway in response to aripiprazole treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, pretreatment with D2R‐specific antagonists did not prevent the apoptosis‐inducing effect of aripiprazole but rather strengthened it, clearly demonstrating that D2R signaling is not responsible for the aripiprazole‐induced apoptosis in breast cancer cells. It has previously been reported that treating mice with haloperidol reduces tau phosphorylation via D2 blockade‐mediated inactivation of AMPK . In this study, breast cancer cells activate the AMPK pathway in response to aripiprazole treatment.…”
Section: Discussionmentioning
confidence: 68%
“…In the current report, we found that in mice homozygous for the P301L transgene, treatment with reboxetine was followed acutely by significant increases in extracellular dopamine concentrations, and contemporaneous increases in the phosphorylation of tau. In our previous work with the Tg4510 mouse, a forebrain expressed P301L model of tauopathy (Santacruz et al 2005), a reduction in phosphorylation of tau was observed following the blockade of the dopamine D 2 receptor with haloperidol (Koppel et al 2016). Similar to the current report, but in a different direction, reductions were observed in PHF1, RZ3, and CP13 phosphotau ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported on a robust decrease in tau phosphorylation in the cortex and striatum of Tg4510 tau mice following 2 and 6 weeks of treatment with haloperidol, a potent dopamine D 2 receptor blocking antipsychotic (Koppel et al 2016). This result suggests that regional extracellular dopamine concentrations may influence tau phosphorylation patterns and that just as agents that block dopamine signaling reduce tau phosphorylation, therapies that increase dopamine signaling may promote it.…”
mentioning
confidence: 99%
“…After being activated by LKB1, AMPK kinases stimulate catabolic and inhibit anabolic processes allowing the cells to adapt to hypoxia by adjusting intracellular ATP ( Ramamurthy and Ronnett, 2006 ). It is reported that blocking the AMPK pathway, reduced tau phosphorylation in a tau mouse model of AD, showing a link between activation of the main cellular responsive kinase to ischaemia and generating p-tau, one of the main hallmarks of AD ( Koppel et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%